Single nucleotide polymorphisms of ADRB2 gene and their association with susceptibility for Plasmodium falciparum malaria and asthma in an Indian population - Saadi, A.V.; Gupta, H.; Angural, A.; Dhanya, S.; Mony, S.; Oberoi, Devesh Varun; D'Souza, S.; Sahoo, R.; Hande, M.; Gopinath, P.; Satyamoorthy, K. (Elsevier, 2013)
The essential route to blood parasitaemia in malaria, erythrocyte invasion is facilitated by activation of the G-protein coupled receptor signaling pathway mediated by the ß2-adrenoreceptor as one of the proteins on the surface of red blood cells. The effectiveness of bronchodilators and inhaled corticosteroids in the clinical treatment for asthma patients also depend on polymorphisms in the ß2-adrenoreceptor gene (ADRB2). In a case control study, individuals affected by Plasmodium falciparum malaria, asthma and controls were tested for association of six ADRB2 single nucleotide polymorphisms (SNPs) viz. rs1042711, rs1801704, rs1042713, rs1042714, rs1042717 and rs1042718, by direct DNA sequencing. The rs1801704 locus was significantly associated with malaria when compared against controls. The rs1042713 polymorphism was associated with forced expiratory flow between 25% and 75% of the FVC in asthma patients, pre (p = 0.048) and post (p = 0.038) treatment measurements. Predicted haplotype of the six SNPs computed from genotype data showed T-T-A-C-G-C conferred significant risk of malaria (p = 0.02) whereas T-T-A-C-G-A was associated with risk of asthma (p = 0.02). The haplotype T-T-G-C-G-C was protective against both malaria (p = 0.02) as well as asthma (p = 0.026) and C-C-G-G-G-C was protective uniquely for asthma (p = 0.04). A significant outcome was that all variant alleles at the SNP loci were part of the haplotype conferring resistance to malaria disease and asthma, except rs1042713 and rs1042718 which showed very high frequency in asthma. The pairwise linkage disequilibrium (LD) estimates showed a distinct LD block of all SNP loci (D' = 1 or >0.8) in malaria patients. This characteristic haplotype block was disrupted in the controls due to non-significant pairwise LD of the SNP loci; and a more extensive disruption of the block was noted in asthma patients. The study provides evidence for the proposed role of ß2-adrenoreceptor mediated molecular mechanisms in etiology of malaria, as well as asthma disease and drug response, for further clinical and therapeutic application studies.